Ravasz László homiletikai elméletének és prédikációs gyakorlatának összevetése - KUN, Mária (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2016)
The Comparison of Homiletical Theory and Preaching Practice in the Work of László Ravasz “I always wanted to be a “homo unius libri”, the author of a single large book written throughout one’s whole life. However, I could not do that. Instead of weaving together all the threads of a single theme into an overall system, each day I had to answer a separate small question and break my great message: the imago mundi into tiny bits and pieces. Rather than carving a huge marble, I had to piece together thousands of colourful pebbles. Here’s, again, a piece of mosaic... I am dedicating my work to those young preachers, – prophets, pastors and doctors –, who are not ashamed to have learnt something from me, and who – I proudly confess – have taught me even more. The beautiful army rushing towards the summit is welcome by the one, who has left the peak and started his way home” Budapest, 1932, the week of Christmas (Preface to Alfa and Omega I) The study analyses the life and work of László Ravasz. It points out what Ravasz considers to be truly important for the preacher, for the audience and also for religious education in general: the subject of the preaching is unquestionably Jesus Christ. As far as his work is concerned, we may note that he considers humour and the well-chosen phrasing of a topic as very important factors of his work. As he says in his Homiletics: “if one cannot find a topic in the biblical text, it means one has got the wrong text, if one cannot find a biblical text for the topic, it means the topic is wrong, or, most probably in both cases, the preacher is unschooled.” He points out that both the preacher and the religion teacher should be goal-oriented. In his Homiletics he stresses that it’s not enough to speak about the subject of the preaching, but the aim should be well-defined as well. He says: “congregational preaching has got an aim, which should be achieved, and it also has a truth, based on which it wishes to achieve its aim." As far as the unfolding of the content is concerned, a three-way branching can be noticed. Regarding the ending, he stresses that it should be so convincing that the audience can say Amen to it.